Management Application for Chendol Bertam - Azzis, Muhammad Amir; Samsudin, Noor Azah (Applied Information Technology And Computer Science, 2026)
Chendol Bertam, a traditional dessert business in Pulau Pinang, Malaysia, has long relied on manual methods to manage inventory and customer bookings. This outdated approach led to frequent stock shortages and booking errors. The main objective of this project was to develop a mobile management application to automate these processes. The application, built using Flutter and Firebase, supports Android devices and enables real-time inventory tracking, low-stock alerts, and a structured booking system. With its user-friendly interface and Agile development approach, the system has significantly improved operational efficiency, minimized manual errors, and laid a foundation for Chendol Bertam’s future business growth